2013
DOI: 10.4103/0970-9185.105798
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical performance of the I-gel with LMA proseal

Abstract: Aim:To compare insertion characteristics of 2 different supraglottic devices [I-gel and Proseal laryngeal mask airway (PLMA)] and to observe any associated complications.Study Design:This prospective, randomized study was conducted in 80 patients [Group I - I-gel insertion (n = 40) and Group P - LMA Proseal insertion (n =40)] of ASA grades I/II, of either sex in the age group 18-65 years. Both groups were compared with respect to ease of insertion, insertion attempts, fiberoptic assessment, airway sealing pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 18 publications
5
108
0
Order By: Relevance
“…(12) A number of other studies reported gastric tube insertion failure in patients who used ProSeal, although it has not been reported in i-gel patients. (16,17,22) Less airway morbidity and fewer complications were observed in the i-gel group as compared with the other two devices in our study. Blood staining of the airway device, which could be indicative of airway mucosal trauma, was observed in the ProSeal and Supreme groups, but not in the i-gel group.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…(12) A number of other studies reported gastric tube insertion failure in patients who used ProSeal, although it has not been reported in i-gel patients. (16,17,22) Less airway morbidity and fewer complications were observed in the i-gel group as compared with the other two devices in our study. Blood staining of the airway device, which could be indicative of airway mucosal trauma, was observed in the ProSeal and Supreme groups, but not in the i-gel group.…”
Section: Discussionmentioning
confidence: 49%
“…(15) Nevertheless, other researchers have previously highlighted the i-gel's higher first attempt success rates and its shorter insertion time as compared with the ProSeal SAD. (16)(17)(18)(19) We postulated that the i-gel SAD should be easier to insert due to its unique gel-like material, shape and contour, buccal stabiliser, and epiglottis blocker that minimises epiglottis downfolding. The faster effective airway time of the i-gel SAD can be explained by the cuffless nature of the device, which obviates the necessity to inflate the cuff during insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Mean time for insertion of PLMA found by Chauhan et al, [27] was 15.13±2.91 seconds in compare with i-gel which was 11.12±1.81 seconds. The result was statistically significant and quite similar to our study.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly Trivedi et al and Chauhan et al found i-gel airway was easier to insert with less attempt when compared to PLMA. 9,12,16,17 Das et al had observed higher number of manipulations to insert LMA than i-gel. 18 In our study device was placed in first attempt in 88% patients of group i-gel compared to 64% of group LMA.…”
Section: -13mentioning
confidence: 99%
“…Mean insertion time for the i-gel was significantly lower than LMA. 12 Wharton et al evaluated the performance of i-gel supraglottic airway device in manikins and anesthetized patients. Their results suggest the i-gel is rapidly inserted in both manikins and patients by an inexperienced person and compares favourably to other supraglottic airways available.…”
Section: -13mentioning
confidence: 99%